First Tuvan abecedaries - Oorzhak, Marina S. (The New Research of Tuva, 2014)
Article describes the first Tuvan textbooks published in Peoples Republic of Tuva (1921-1944). Special attention is paid to the aspiration of Tuvan people to knowledge.
Keywords: Tuvan language; Tuvan abecedary; Peoples Republic of Tuva; Tuvan written language; literacy project